Challenges of Health and Physical Education in Teacher Education Program - Adhikari, Yadav Raj (Shikshya Sandesh, 2023)
Health and Physical Education (HPE) is losing appeal despite of its real need in teacher education. In this context, this study aims to explore the teachers’ perceptions towards the importance of health and physical education and its challenges to gain prescribed objectives. To accomplish the objectives, phenomenological research design under qualitative inquiry was applied. Unstructured interview was taken with teachers to gather information. Informants were selected purposively from Prithvi Narayan Campus (PNC) which is the largest constituent campus under Tribhuvan University of Nepal. The study explored that health and physical education is always emerging, dynamic, daily life related and life skills based education but phenomena is different. For this phenomena various constrains are responsible, out of them student, teacher, curriculum, pedagogies, evaluation system and job related challenges are major constrains.